Meaning-Based Coping and Spirituality During the COVID-19 Pandemic: Mediating Effects on Subjective Well-Being - Arslan, Gökmen; Yıldırım, Murat (Frontiers in Psychology, 2021)
Coronavirus pandemic has significantly affected the Turkish population. During pandemic, people with high coronavirus stress are at risk of experiencing poor subjective well-being. There is no research investigating the role of meaning-based coping and spirituality in explaining the link between coronavirus stress and subjective well-being. This study examined the mediating roles of meaning-based coping and spiritual well-being in the link between coronavirus stress and subjective well-being in young adults during COVID-19 pandemic. The sample included 427 young adults (71% female), ranging age between 18 and 48 years (M= 21.06; SD= 2.62). Turkish young adults completed an online survey including measures of coronavirus stress, subjective well-being, meaning-based coping, and spiritual well-being. The results indicated that greater meaning-based coping and spiritual well-being mediated decreases in the adverse impacts of coronavirus stress on subjective well-being. These results suggest that the importance of combination of meaning-based coping and spirituality processes mitigate the adverse effects of stress on well-being during coronavirus pandemic. Interventions focusing on meaning-based coping and spirituality in those experiencing high coronavirus stress are urgently needed to improve mental health and well-being of young adults.